2016
DOI: 10.1007/s00345-016-1832-4
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in renal cortical neoplasms: an updated evaluation from a single institution

Abstract: Purpose To examine the incidence of secondary primary malignancies in patients with renal cortical neoplasms. Methods Between January 1989 and July 2010, 3647 patients underwent surgery at our institution for a renal cortical neoplasm and were followed through 2012. Occurrence of other malignancies was classified as antecedent, synchronous, or subsequent. All patients with antecedent malignancies (n = 498) and a randomly selected half of those with synchronous malignancies (n = 83) were excluded. The expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Lane et al [21] reported DFS of 96.9% and 92.3% in LPN and open PN subgroups, respectively, in patients with minimum 5-yr follow-up. The DFS rate in our cohort was slightly inferior compared with the mentioned series, but it has to be emphasized that OS in our series is 95.1% despite 29% patients having a history of another neoplasia [24]. Moreover, the follow-up schedule in our patients included lung CT, which was not routinely performed in other series [10,11].…”
Section: Discussioncontrasting
confidence: 55%
“…Lane et al [21] reported DFS of 96.9% and 92.3% in LPN and open PN subgroups, respectively, in patients with minimum 5-yr follow-up. The DFS rate in our cohort was slightly inferior compared with the mentioned series, but it has to be emphasized that OS in our series is 95.1% despite 29% patients having a history of another neoplasia [24]. Moreover, the follow-up schedule in our patients included lung CT, which was not routinely performed in other series [10,11].…”
Section: Discussioncontrasting
confidence: 55%
“…A total of 40 articles (33 retrospective cohorts, 5 retrospective case-controls and 2 prospective cohorts) including 1,613,945 cancer patients with 15 distinct primary cancers were included in the analysis [ 5 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The kidney-breast cancer link was inconsistent in previous publications. Murray et al recently found a lower than expected rate of BC in renal cortical neoplasms using a 90 day of latency [37]. While a study based on the European Prospective revealing an excessive risk of kidney cancer among BC survivors [38].…”
Section: Plos Onementioning
confidence: 96%